(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article substantiates the need to improve budget management through the introduction of a process-oriented approach. Built a conceptual model of effective management of a trading company in the transition to process-oriented budget management. Presents the process of transition from a traditional to a process-oriented budget management, including six stages. Each stage is characterized by a clear sequential shift. So in the process of implementing this mechanism conceptual model was built effective management of a trading company in the transition to process-oriented budget management; description of business carried out activities of commercial enterprises; It developed a business process system and the definition of the functions of each of them; formed a chain of creation of enterprise value; developed mechanisms for budget management system restructuring and the organizational structure in the transition from traditional to activity-based budget management; described the allocation of responsibility for business processes budgets. In order to determine the feasibility study developed a mechanism of transition disadvantages in the traditional budget management in the pros in the transition to process-oriented.